2017
DOI: 10.1097/rhu.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Impeding the Use of Non-pharmacological, Non-surgical Care in Hip and Knee Osteoarthritis

Abstract: Healthcare providers report multiple barriers impeding non-pharmacological, non-surgical care for patients with knee and hip OA. To overcome these barriers, education focused on initiating and supporting lifestyle changes, promotion of interventions according to evidence-based recommendations, and improved organization of care are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 22 publications
5
49
0
Order By: Relevance
“…Briggs et al / Osteoarthritis and Cartilage 27 (2019) 788e804 analysis of the qualitative data ensured all relevant issues were coded and meta-synthesised, providing important foci for training resources in OA care and considerations for developing models of care for OA in Australia, New Zealand and Canada. Although consistent with aligned research 32,44,52 , the outcomes reported should be considered in the context of recruitment limitations, including a selection bias towards Australian clinicians and no representation from Canadian GPs, and limited samples sizes for clinician groups. This selection bias may have led to an over-or under-estimation of the frequency of barriers reported.…”
Section: Discussionmentioning
confidence: 69%
“…Briggs et al / Osteoarthritis and Cartilage 27 (2019) 788e804 analysis of the qualitative data ensured all relevant issues were coded and meta-synthesised, providing important foci for training resources in OA care and considerations for developing models of care for OA in Australia, New Zealand and Canada. Although consistent with aligned research 32,44,52 , the outcomes reported should be considered in the context of recruitment limitations, including a selection bias towards Australian clinicians and no representation from Canadian GPs, and limited samples sizes for clinician groups. This selection bias may have led to an over-or under-estimation of the frequency of barriers reported.…”
Section: Discussionmentioning
confidence: 69%
“…In their clinical trial, comparing an optimized non-operative treatment strategy with an optimized non-operative treatment strategy combined with total knee replacement, only 26% of those in the non-operative group subsequently decided to undergo surgery during the following 12 months. Rheumatologists, orthopedic surgeons, and general practitioners considered that a barrier to referring patients with OA to physiotherapy is that patients receive non-evidence-based passive treatment modalities, instead of exercise therapy (Selten et al 2017). Correspondingly, only 2 in 3 patients in our study had received exercise as part of their physiotherapy treatment.…”
Section: Discussionmentioning
confidence: 93%
“…More recent studies have, however, established that patients with severe radiographic OA grades can also achieve pain relief and functional improvement with exercise (Juhl et al 2014, Skou et al 2015a, and even large exercise loads do not seem to be harmful for the cartilage in the osteoarthritic knee (Bricca et al 2018). Even though a more recent report suggests that physiotherapists are convinced by this contemporary knowledge (Spitaels et al 2016), another study pointed at several healthcare providers doubting the real benefits of exercise (Selten et al 2017). Furthermore, lack of support, or conflicting information from different healthcare providers, were found to be important barriers for patients to adhere to exercise therapy (Kanavaki et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of a clear deficit in professional capabilities that limits the implementation of optimal evidencebased OA care in healthcare 24 . Several major barriers to the implementation of evidence-based OA care have been identified 24,25 . Important common themes include that clinicians feel under-prepared in terms of knowledge and skills to deliver treatments recommended by OA management guidelines, and clinicians report doubts about the effectiveness of treatments for OA.…”
Section: Discussionmentioning
confidence: 99%